Small sample properties of maximum likelihood versus generalized method of moments based tests for spatially autocorrelated errors - Peter Egger; Mario Larch; Michael Pfaffermayr; Janette F. Walde (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper undertakes a Monte Carlo study to compare MLE-based and GMM-based tests regarding the spatial autocorrelation coefficient of the error term in a Cliff and Ord type model. The main finding is that a Wald-test based on GMM estimation as derived by Kelejian and Prucha (2005a) performs surprisingly well. Our Monte Carlo study indicates that the GMM Wald-test is correctly sized even in small samples and exhibits the same power as their MLE-based counterparts. Since GMM estimates are much easier to calculate, the GMM Wald-test is recommended for applied researches.
Keywords: C12; R10; C21; 330; spatial autocorrelation; hypothesis tests; Monte Carlo studies; maximum likelihood estimation; generalized method of moments; Maximum-Likelihood-Methode; Momentenmethode; Autokorrelation; Statistischer Test; Theorie